2021
DOI: 10.1080/11101849.2021.1925442
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of copeptin and psychological stress among healthcare providers during COVID-19 pandemic

Abstract: Background:The COVID-19 pandemic created a remarkable impact on healthcare providers (HCP) both physically and psychologically. Perceived psychological stress (PSS) influences the homeostatic equilibrium, involving activation of the sympathetic nervous system and hypothalamus pituitary adrenal (HPA) axis. Copeptin, C-terminal portion of Vasopressin (AVP) precursor is stable; however, evidence about impact of PSS on copeptin levels is limited. Aim: The aim of this study was to estimate the influence of psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…We found that serum copeptin levels were significantly higher in those with moderate and severe stress as compared to those with mild stress following recovery from COVID. Demerdash and co-workers studied stress in healthcare workers involved in the care of COVID-19 by measuring stress by perceived stress score (PSS) questionnaire and copeptin ( Demerdash et al, 2021 ). The study revealed that baseline copeptin levels pre-quarantine were significantly increased and positively correlated with high stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that serum copeptin levels were significantly higher in those with moderate and severe stress as compared to those with mild stress following recovery from COVID. Demerdash and co-workers studied stress in healthcare workers involved in the care of COVID-19 by measuring stress by perceived stress score (PSS) questionnaire and copeptin ( Demerdash et al, 2021 ). The study revealed that baseline copeptin levels pre-quarantine were significantly increased and positively correlated with high stress.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that baseline copeptin levels pre-quarantine were significantly increased and positively correlated with high stress. A decline in serum copeptin and PSS was observed following a decrease in stress post-quarantine ( Demerdash et al, 2021 ). The role of copeptin as a stress biomarker in subjects who had recovered from COVID has not been explored so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endocrine stress conditioning is mediated by many hormones, including the AVP and cortisol through the activation of the hypothalamic–adenohypophyseal axis. Copeptin is a biochemical mirror to the AVP as being synthesized from the same ancestor gene, preproprotein precursor and stoichiometrically released, in addition to being remarkably stable in blood samples with the easier biochemical assay [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Together with AVP, copeptin is secreted in an equimolar amount from the neurohypophysis in response to AVP release stimulating conditions [ 15 ]. Due to the short half-life and instability of AVP in blood, copeptin is a preferred sensitive and stable surrogate biomarker for estimating AVP release [ 16 , 17 ].…”
mentioning
confidence: 99%